Comprehensive Analysis of Patient Engagement in General Healthcare Practices and Study of Environmental Health Impacts on General Healthcare Services - Alkhomsan, Salem Saleh Ali; Alyami, Ahmed Abdullah Ahmed; Alkastabn, Ibrahim Saleh; Alyami, Nasser Saleh M; Al Kostoban, Mohammed Saleh; Sayari, Majed Salem Yaslem; Majrashi, Mohammed Ali Mohammed; Almuhri, Sultan Nasser Mahdi; Bakri, Yahya Attiya Ahmed; Alkastabn, Saud Saleh (Journal of Ecohumanism, 2024)
This paper critically reviews patient participation in general healthcare practices and the effects of environmental health on the operations of health facilities. Patient engagement is important to achieve better patient results, increase the effectiveness and efficiency of treatment, and minimize the charges incurred in the process. At the same time, managing factors like pollution, climate change, and natural disasters indirectly or directly impact healthcare provision. The literature review investigates current engagement best practices concerning the patient according to the abovementioned goals. Also, it looks at how environmental health impacts health system objectives such as transport and other infrastructural support, expenditure on health, and patients. The conclusions drawn are according to the literature studied, case analysis, and current statistics, as evidenced by tables, figures, and graphs where appropriate to highlight trends and effects.